Processo de trabalho de gestores da atenção primária à saúde no contexto da pandemia da covid-19 - Apparecido, Roberta Silva (2023)
Understanding the work process of PHC managers in the context of the pandemic, based on the identification and analysis of the actions taken, the organization of work, as well as the potentialities and limitations from the manager's point of view, is extremely important for understanding the dynamics of the Unified Health System in emergency situations. The aim is to answer how the new coronavirus pandemic influenced the actions carried out by the local PHC management and how the emergency measures had an impact on the work process of the managers. Objective: This research aims to understand the work process of Primary Health Care (PHC) managers in the context of the COVID-19 pandemic. This is a qualitative, descriptive exploratory study, with data collection carried out through semi-structured interviews with PHC managers of a Technical Health Supervision (STS), in the city of São Paulo. Thematic content analysis was carried out in the light of the theoretical framework of the health work process in PHC and health management in PHC. Eleven interviews were carried out through the Google Meet platform, from which the following themes were constructed: 1) actions of PHC managers in the context of the COVID-19 pandemic: reorganization of the work process based on new actions, new strategies developed to optimize the work process and daily management for new work processes; 2) perceptions of PHC managers in the context of the COVID-19 pandemic: limitations and potential. The managers' perception of the process and work of the PHC teams during the COVID-19 pandemic generated knowledge for future health events, especially with regard to the reorganization of the teams' work. New flows for managing symptoms, information gaps, maintaining quality in the face of adversity and not interrupting care for chronic patients, the daily matrix of new processes, the illness of workers, motivating the engagement of professionals in their teams were challenges that had an impact in the work routine and also exhausted them, but at the same time made them develop valuable work tools.